Opportunities For Micro, Small and Medium Enterprises in Increasing Sales Using Information and Social Media in The Nagan Raya District Area - Ajidan, Ajidan (Jurnal Ilmiah Teunuleh, 2025)
This research aims to analyze the use of information and social media in improving micro, small and medium enterprises (UMKM) in Nagan Raya Regency. The research results show that although the Nagan Raya Regency government has developed an information system such as the sidumnara website to centrally integrate MSME data, the use of websites as a means of marketing MSME products is still not effective. This is caused by the public's low interest in accessing government websites which is influenced by factors such as content classification, navigation and readability that are less than optimal. On the other hand, social media such as Instagram, TikTok and Facebook are more popular with the public because of their more attractive appearance and ability to reach a wider audience. Apart from that, the demographic bonus with the high percentage of the population of productive age in Nagan Raya Regency opens up great opportunities for the use of social media in product marketing. Therefore, although websites can help in the administration and management of MSME data, social media is a more effective platform for marketing products and increasing interaction with consumers. This research concludes that creative use of social media can encourage UMKM to optimize their sales, exceeding the achievements obtained through traditional marketing methods.